Intradialytic exercise in end-stage renal disease: An umbrella review of systematic reviews and/or meta-analytical studies. (June 2021) - Bündchen, Daiana Cristine; Sousa, Helena; Afreixo, Vera; Frontini, Roberta; Ribeiro, Oscar; Figueiredo, Daniela; Costa, Elísio
Objectives: This umbrella review aimed to understand the clinical benefits and adverse events associated with different modalities of intradialytic exercise in patients with end-stage renal disease undergoing hemodialysis. Data Sources: The search was performed until September 10th, 2020 on Scopus, Web of Science, the Cochrane Database, CINAHL, and PubMed. Methods: This umbrella review was conducted following the PRISMA guideline statement. The methodological quality of the reviews was assessed with the AMSTAR-2. Standardized mean differences with 95% confidence intervals were estimated. The I-squared statistic was used to assess heterogeneity and the Eggers' test was performed to test asymmetry/small-study effects. Results: Eleven reviews were included and 48 unique meta-analyses were examined. Nine were supported by suggestive evidence ( P  < 0.05, small heterogeneity, absence of small-study effects, and excess significance bias). Clinical benefits were found for functional capacity associated with aerobic exercise ( d  = 0.81; k  = 6), resistance training ( d  = 0.58; k  = 6), neuromuscular electrical stimulation ( d  = 0.70; k  = 5), and inspiratory muscle training ( d  = 1.13; k  = 2), measured by the distance covered in the 6-minutes walking test. This outcome was also associated with aerobic exercise ( d  = 0.28; k  = 7) and combined exercise, measured by VO2peak ( d  = 1.01; k  = 5) and by the duration of the cardiopulmonary test ( d  = 1.07; k  = 4). Isometric quadriceps muscle strength improved with neuromuscular electrical stimulation ( d  = 1.19; k  = 7) while patients' perception of vitality improved with combined exercise ( d  = 0.60; k  = 3). Conclusions: Suggestive evidence was found for the associations between various modalities of intradialytic exercise and functional capacity. Combined exercise was associated with improvements in physical and psychosocial variables. Few or no adverse events were reported.